Pengembangan Modul Admin dengan Framework Laravel pada Website Dinas Komunikasi dan Informatika Kota Bogor - Salsabilla Maharani Khotibatunnisa; Umi Rochayati (Journal of Information Technology and Education (JITED), 2025)
This research aims to: (1) Develop an Admin Module on the Website of the Communication and Information Office of Bogor Municipality. (2) Knowing the Quality of the Admin Module on the Website of the Communication and Information Office of Bogor Municipality using ISO 25010 testing with functional suitability, performance efficiency, usability, reliability, and maintainability characteristics. Development research uses development with the Agile Modeling method which has several stages including the requirements stage, design stage, development stage, testing stage, and review stage. The resulting product is the Admin Module on the Website of the Communication and Information Office of Bogor Municipality based on the website. Tests carried out using ISO 25010 testing with functional suitability characteristics using the Expert Validation Test by in the field of development or software, performance efficiency tested using the GTMetrix application, usability tested by respondents from the Communication and Informatics Office of Bogor Municipality, reliability using WAPT Pro 5.1 software, and maintainability using PHPMetrics software.